1996
DOI: 10.1111/j.1467-646x.1996.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Ability of Geographic Segment Information at the Country, Continent, and Consolidated Levels

Abstract: This study examines whether geographic information disclosed at an increasingly disaggregated level (specifically, consolidated vs. continent vs. country) results in increased predictive ability of company operations (specifically, sales, gross profit, and earnings). Multinational corporations (MNCs) are formed using a simulated merger approach by combining the annual operating results of six individual firms, one from each of six countries. This approach makes it possible to compare the forecasting accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
2
18
0
5
Order By: Relevance
“…Street et al (2000) report that the consistency of segment information and the number of total segments reported increased significantly with the introduction of SFAS 131. Based on these findings, the authors conclude that business reporting improved with SFAS 131 (see also Herrmann and Thomas, 2000;and Berger and Hann, 2003). Similarly, a 1998 report by Bear Stearns emphasizes the improvement in the consistency of descriptions of the business throughout the president's letter, management discussion and analysis, and notes.…”
Section: (I) Brief Background On Sfas 131mentioning
confidence: 72%
See 3 more Smart Citations
“…Street et al (2000) report that the consistency of segment information and the number of total segments reported increased significantly with the introduction of SFAS 131. Based on these findings, the authors conclude that business reporting improved with SFAS 131 (see also Herrmann and Thomas, 2000;and Berger and Hann, 2003). Similarly, a 1998 report by Bear Stearns emphasizes the improvement in the consistency of descriptions of the business throughout the president's letter, management discussion and analysis, and notes.…”
Section: (I) Brief Background On Sfas 131mentioning
confidence: 72%
“…Regarding geographic segment disclosures, prior research suggests that, under certain conditions, such disclosures potentially enhance predictability of consolidated amounts (e.g., Balakrishnan et al, 1990;Nichols et al, 1995;Herrmann, 1996;and Lobo et al, 1998). However, user groups complained that firms' disclosure practices under SFAS 14 were inadequate and research has shown that investors did not use SFAS 14 geographic segment earnings disclosure in valuing securities (Boatsman et al, 1993).…”
Section: (Ii) Hypothesesmentioning
confidence: 94%
See 2 more Smart Citations
“…3 Only Canada and the U.K. were disclosed by a sufficient number of firms to be incorporated in tests of association with security prices (Boatsman, Behn and Patz, 1993;Nichols, Tunnell and Waldrup, 1996;Thomas, 2000). Using a simulation approach to assess the predictive ability of geographic segment information, Herrmann (1996) is able to expand this group of countries to include France, Germany, and Japan. In general, the results of these studies suggest that individual country disclosures can be useful.…”
Section: Individual Country Disclosuresmentioning
confidence: 99%